2016
DOI: 10.1002/hipo.22596
|View full text |Cite
|
Sign up to set email alerts
|

Memory retrieval along the proximodistal axis of CA1

Abstract: The proximal and distal segments of CA1 are thought to perform distinct computations. Neurons in proximal CA1 are reciprocally connected with the medial entorhinal cortex (MEC) and exhibit precise spatial firing. In contrast, cells in distal CA1 communicate with the lateral entorhinal cortex (LEC), exhibit more diffuse spatial firing and are affected by the presence of objects in the environment. To determine if these segments make unique contributions to memory retrieval, we examined cellular activity along t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
43
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 28 publications
6
43
1
Order By: Relevance
“…Using a genetic memory trace strategy (Cazzulino et al, 2016; Denny et al, 2014; Josselyn et al, 2015), we demonstrated variations in the engagement of CA3 neurons in memory recall along the CA3 transverse axis. Our findings support the results of a recent study in showing that CA3c has weaker reactivation compared to more distal regions of CA3 (Nakazawa et al, 2016). By distinguishing between CA3a and CA3b, we find that cellular reactivation efficiency peaks in CA3b.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Using a genetic memory trace strategy (Cazzulino et al, 2016; Denny et al, 2014; Josselyn et al, 2015), we demonstrated variations in the engagement of CA3 neurons in memory recall along the CA3 transverse axis. Our findings support the results of a recent study in showing that CA3c has weaker reactivation compared to more distal regions of CA3 (Nakazawa et al, 2016). By distinguishing between CA3a and CA3b, we find that cellular reactivation efficiency peaks in CA3b.…”
Section: Discussionsupporting
confidence: 93%
“…A functional divergence along the proximodistal axis has also been observed in CA1 (Henriksen et al, 2010; Igarashi et al, 2014; Masurkar et al, 2017; Nakazawa et al, 2016). The distinctive behavioral roles and physiological properties of distal versus proximal CA1 are primarily attributed to differences in the sources of synaptic input.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Relative to distal CA1 cells, place cells in proximal CA1 are more spatially selective, carry more spatial information, show higher rate remapping following changes to the environment, and exhibit stronger theta phase-coupling with spatially tuned MEC cells (Henriksen et al, 2010;Hartzell et al, 2013;Oliva et al, 2016). Relative to distal CA1, proximal CA1 also shows higher immediate early gene (c-fos) activation during memory retrieval for spatially-cued contextual fear, and proximal (but not distal) CA1 lesions abolish such memory retrieval (Nakazawa et al, 2016).…”
Section: Introductionmentioning
confidence: 99%